Bulletin of the Executive committee of the Communist International
Russian ed.: Bjulleten' isponitel'nogo Komiteta kommunističeskogo Internacionala (ZO 16086). - German ed.: Bulletin des Exekutiv-Komitees der Kommunistischen Internationale (ZO 16087).